Polarisation and its importance in the analysis of the contemporary foreign politics of the Republic of Poland - Wicha, Tomasz (Одесса, 2015)
The analysis of the concept of a friend and an enemy helps to categorise and understand the ideas that bother the decidents who study international and internal affairs. Polarisation can be exemplified by natural contrasts (even from everyday life) and by the contrasts in politics. Both of the concepts in polarisation classified the idea and depicted the indispensable notions of a friend and an enemy that can coexist in political realia.
Wicha T. Polarisation and its importance in the analysis of the contemporary foreign politics of the Republic of Poland / T. Wicha // Международное право развития: современные тенденции и перспективы : материалы междунар. науч.-практ. конф. (г. Одесса, 17 июня 2015 г.) ; НУ «ОЮА» ; Кафедра междунар. права и междунар. отношений. – Одесса, 2015. – С. 186-189.